Manajemen Pengolahan Limbah Rumah Makan dalam Upaya Mitigasi Pencemaran Lingkungan - Dwi Jayadi Kurniawan; John Bimasri; Wartono Wartono (Westscience Press, 2026)
Restaurants are one of the sources of waste generation that have the potential to cause environmental pollution. Their operational activities produce various types of waste, including liquid, solid, and gaseous waste. This study aims to identify the types of waste generated by restaurants and to evaluate the waste management systems applied.The research was conducted using a survey method with a quantitative descriptive approach from July to August 2025. The research location was determined purposively, with the objects consisting of liquid waste, solid waste, and oil waste, while the subjects were restaurant owners and employees. The independent variables in this study include types of waste and waste management techniques, while the dependent variables include the environmental impacts of waste and the level of compliance of restaurant managers with environmental quality standards.Data were collected through observation, interviews, and questionnaires, and then analyzed quantitatively using descriptive statistics. The results indicate that restaurants generate various types of waste with significant potential as sources of environmental pollution. The waste produced includes liquid waste, organic and inorganic solid waste, oil waste, and light hazardous waste. Restaurant operational activities can also lead to pollution of water, soil, and air, as well as noise and visual disturbances. Efforts to control environmental pollution are carried out through the implementation of simple wastewater treatment systems (WWTP), biological treatment, and the application of the 3R principles (reduce, reuse, recycle).